Implementasi Model Role Play dan Simulasi dalam Meningkatkan Aktivitas Belajar PAI di Sekolah Dasar - Harahap, Fitri E; Purqoni, Aang; Ifah Hadijah; Aryani, Wiwik Dyah (Papanda Publisher, 2025)
Conventional teaching methods are still widely used in Islamic Religious Education (IRE) classes at the elementary level, resulting in students’ low engagement and passive learning behavior. This study aims to analyze the implementation of Role Play and Simulation models in enhancing students’ learning activities. Employing a qualitative descriptive design, data were collected through interviews, observations, and document analysis involving one IRE teacher and two students at SDN Palintangjaya, Bandung Regency. The findings reveal that the Role Play model is more frequently applied to moral and prophetic stories due to its flexibility and adaptability, while the Simulation model is particularly effective for practical materials such as congregational prayer. Both models enhance students’ cognitive, affective, and psychomotor engagement. Supporting factors include school leadership support, student enthusiasm, and adequate facilities, whereas time constraints and large class sizes pose significant challenges. These findings affirm the relevance of experiential learning approaches in improving IRE teaching quality and strengthening character education at the elementary level.